The Used Of UAV-Based Photogrammetry For Discontinuity Mapping At Hume Cement Quarry, Malim Nawar Perak - Yaacob, Solihin (Universiti Sains Malaysia, 2018)
This study aimed to conduct the geotechnical mapping of discontinuities, to analyze the photogrammetry method and to understand the criteria needed for geological mapping. An Unmanned Aerial Vehicle (UAV) was used for geotechnical mapping while Agisoft Photoscan 3-D, MATLAB, CloudCompare and Rocscience Software was used to analyze the photogrammetry method as comparison with conventional mapping. The study site is at Hume Cement quarry site where 26 survey windows were identified comprise the whole quarry pit with each window involved approximately 30 m parameter length. In total of 26 windows, rose diagram was used to represent the dominant joint set in each window. So, it can be concluded that the major orientation of the discontinuity feature for this study site is in NNW-SSE direction. Furthermore, photogrammetry method also provides a more reliable result compared to conventional mapping, while the results of rosette diagram for UAV method showed a similarities compared to the conventional mapping. As a conclusion, photogrammetry method with advantages of UAV using drone technology is recommended because it allows more accurate characterization of rock mass.